Electronic Payment System and Poor Fees Collection in Universities in South Eastern States of Nigeria - Anyanwu Kingsley N (International Journal on Economics, Finance and Sustainable Development, 2022)
This study has examined electronic payment system and fees collection in universities in South Eastern Nigeria. A study of five selected universities in South Eastern Nigerian was used. Objectives, research questions and hypotheses were formulated and they were analyzed. Questionnaire was the major source of data collection and copies of this questionnaire were distributed to the staff of the selected organizations. The Analysis of Variance (ANOVA) was used to analyze the data and the Statistical Package for Social Science (SPSS) was as well used. The findings show that mobile banking has effect on efficient collection of fees in universities in South Eastern Nigeria, and that there is significant relation between internet banking and efficient collection of fees in universities in south eastern Nigeria. Based on the findings, the study recommends that Universities should understand that making online payments and coming also in person to confirm such payment defies the intent of electronic payment and at such, they should look for easier online methods of confirmation of payments. Also, Online payment system is capital intensive and universities should make sure they have the required equipment and personnel, before adopting such payment method